Studi Pelapisan Krom Pada Baja Karbon Dengan Rapat Arus 5 Ampere Tegangan 12 Volt Dan Variasi Waktu Pencelupan 10, 20, 30, 40, 50 Menit - Salim, Nurdin, Tri Widodo Besar Riyadi. ST. MSc. Ph.D (2016)
The purpose of this study was to investigate the influence of process parameters, namely chrome plating immersion time to microstructure and surface hardness of the product. The study was conducted with an experimental method using electrodes carbon steel, chrome electrolyte solution, additives, direct current source, and other plating equipments. Chrome product microstructure was observed to analyze the thickness of the coating. Evaluation of the mechanics carried out to measure the hardness. The results of this study will add to knowledge for industrial players to improve product quality of chrome whish is good for protection against corrosion, increased wear resistance, as well as to add value decorative product.